The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
DOI: 10.30707/etd2013.chang.k
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Student Satisfaction In Different Learning Deliveries

Abstract: This study addressed the relationship between student satisfaction and four interaction variables-student-content, student-instructor, student-student, and studenttechnology-in online, blended, and traditional learning settings. Demographics, previous experience with the Internet, and discussion-board applications were also investigated.There were 916 respondents, including 185 in online settings, 90 in blended settings, and 641 in traditional settings, to Strachota's (2002) Online Satisfaction Survey.Particip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
14
0

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 82 publications
4
14
0
Order By: Relevance
“…The findings above are in consonance with the research of Chang (2013), Chiu et al (2007) and Chen et al (2008). Chang (2013) and Chen et al (2008) expressed that students' satisfaction is dependent on the interaction between learners and teachers. As shown in Table 1, contact with teachers has a high satisfaction among students at mode of 4.…”
Section: Respondents' Characteristicssupporting
confidence: 89%
See 1 more Smart Citation
“…The findings above are in consonance with the research of Chang (2013), Chiu et al (2007) and Chen et al (2008). Chang (2013) and Chen et al (2008) expressed that students' satisfaction is dependent on the interaction between learners and teachers. As shown in Table 1, contact with teachers has a high satisfaction among students at mode of 4.…”
Section: Respondents' Characteristicssupporting
confidence: 89%
“…The manner in which a course is delivered has impact on students' satisfaction (Chang, 2013;Wilson, Cordry & King, 2004). Shea, Pickett and Pelz (2003) also asserted that the course delivery and course design have impact on the level of students' satisfaction.…”
Section: Empirical Review Of Factors Affecting Students' Satisfactionmentioning
confidence: 99%
“…It is plausible that hybrid learning satisfaction is affected by course content satisfaction given that students majoring in finance may be more satisfied with finance‐related course content than other students. Moreover, other studies also showed that students' majors play an important role in learning experience as well (Chang, 2011; Hsieh, 2014). Therefore, the present study suggests that if major is not a variable of interest, it must be experimentally controlled or at least statistically controlled as the present study did.…”
Section: Discussionmentioning
confidence: 94%
“…The results show that there is a relationship between physical environment factors and student learning satisfaction. Furthermore, according to Chang (2011), if students come across problems, they would also affect their satisfaction. Chokor (2015) viewed that thermal comfort and acoustic quality, and similar performance in lighting level, indoor air quality does affect the overall satisfaction on the facilities.…”
Section: Indoor Environmental Quality (Ieq) and Student Learning Satisfactionmentioning
confidence: 99%